Ponctuation, édition, interprétation : l’exemple du point-virgule dans Bouvard et Pécuchet - Anne Herschberg Pierrot (Flaubert: Revue Critique et Génétique)
The autograph unfinished manuscript of Bouvard et Pécuchet presents a personal system of signs, prior to a future re-reading for publication. This provides an interesting field for the study of Flaubert’s punctuation. Indeed, the manuscript presents a partially suspensive punctuation, mainly rhythmic, which cannot be printed as it is. But on what criteria can we base editorial choices? This article studies the status of one specific element: the semicolon. We will try to elucidate these choices which for an unfinished work always involve interpretation and individual decisions.